Pragmatismo e economia: elementos filosóficos para uma interpretação do discurso econômico - GALA, Paulo Sérgio de Oliveira Simões (2012)
This paper brings elements from the pragmatic philosophy to the debate on methodology in economics, with a specific concern on the theory of truth and its connection with epistemology. After briefly discussing the contributions of William James, John Dewey, Charles Sanders Peirce and the works of Willard Quine and Richard Rorty in this area, we point out to some of the influences that this school of thought may have had on the work of important economists such as John M. Keynes, Milton Friedman and Thorstein Veblen. We then conclude with some reflections that may be useful for research made by economists.